OFFLINE ADVERTISING VERSUS ONLINE ADVERTISING - BARBU, Cristina Mihaela; PONEA, Ștefan; BOGDĂNOIU, Cristiana Luminiţa (Theoretical and Practical Research in Economic Fields; Vol 10 No 2 (2019): TPREF, Volume X, Issue 2(20), Winter 2019, 2019)
The starting point of the article is the following: is the online environment appropriate to the requirements and needs for affirmation and efficiency of advertising considered a concern by itself? How effective is this advertising model? How can we demonstrate the effectiveness of online advertising? What new does this "new media" bring? The present paper aims to define online advertising in the light of the environment in which it is developed but also of the promotion tools and to present the stages of designing an advertising campaign conducted exclusively in the online environment.